2019
DOI: 10.11646/zootaxa.4671.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Labrys khuzestanensis n. sp. (Nematoda, Tylenchidae), a new member of the genus with large labial plate

Abstract: Labrys khuzestanensis n. sp. was recovered from the rhizosphere of a palm tree in southwestern Iran and described using morphological and molecular data. The new species was characterized by combination of the following features: its 590–675 μm long body, finely annulated cuticle in light microscopy (LM), lateral field with two smooth incisures, cephalic region dorso-ventrally flattened with protuberant, elongate and laterally extended labial plate, appearing a V-shaped piece in lateral view, amphidial opening… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 583 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…Our 28S rDNA tree supported the position of Discopersicus in the subfamily Boleodorinae (Khan, 1964) in close affinity with the genera Basiria and Boleodorus. The monophyly of the subfamily Boleodorinae was confirmed as concluded in former researches (Eisvand et al, 2019;Hosseinvand et al, 2020a, b, c;Panahandeh et al, 2019;Yaghoubi et al, 2016). The new species formed a strongly supported clade with Boleodorus spp., while, in Yaghoubi et al (2016) study, D. iranicus was placed inside Neopsilenchus spp.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our 28S rDNA tree supported the position of Discopersicus in the subfamily Boleodorinae (Khan, 1964) in close affinity with the genera Basiria and Boleodorus. The monophyly of the subfamily Boleodorinae was confirmed as concluded in former researches (Eisvand et al, 2019;Hosseinvand et al, 2020a, b, c;Panahandeh et al, 2019;Yaghoubi et al, 2016). The new species formed a strongly supported clade with Boleodorus spp., while, in Yaghoubi et al (2016) study, D. iranicus was placed inside Neopsilenchus spp.…”
Section: Discussionsupporting
confidence: 82%
“…Khuzestan province is located in southwest of Iran, and with arid and warm climate, has an important role for production of agricultural products in Iran. A large number of nematodes have been described from this province ( Azimi and Pedram, 2020 ; Eisvand et al, 2019 ; Ghaderi and Karegar, 2016 ; Hosseinvand et al, 2019, 2020a ; Panahandeh et al, 2019 ). Family Tylenchidae Örley, 1880 is one of the most plentiful and diverse nematode groups recovered in soil habitats, where they may represent up to 30% of the nematode abundance in any given soil sample ( Qing et al, 2018 ).…”
mentioning
confidence: 99%
“…In previous molecular phylogenetic analyses, different placements for Cephalenchus, Eutylenchus excretorius or Cephalenchus + Eutylenchus excretorius clade were resolved using different markers (Subbotin et al, 2006;Bert et al, 2008;Holterman et al, 2009;Palomares-Rius et al, 2009;Panahandeh et al, 2015;Pereira et al, 2017). Moreover, questions already being raised regarding the placement of these two genera in Tylenchoidea (Örley, 1880;Siddiqi, 2000;Subbotin et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, most tylenchids were identified based solely on morphological characters (Geraert, 2008), which led to taxonomic confusions within the family (Qing and Bert, 2019). However, in recent years, DNA-based techniques have been extensively used for taxonomic studies of tylenchids (Bert et al, 2010;Pereira and Baldwin, 2016;Pereira et al, 2017;Panahandeh et al, , 2019Qing and Bert, 2019).…”
mentioning
confidence: 99%
“…The taxonomic studies on the members of the family Tylenchidae reported from Iran are well documented and discussed in Karegar (2018). Some other species of the genera Miculenchus Andrássy, 1959 (Panahandeh et al ., 2019a), Coslenchus Siddiqi, 1978 (Hosseinvand et al, 2019), Labrys Qing & Bert, 2018 (Panahandeh et al ., 2018, 2019b), Sakia Khan, 1964b (Panahandeh et al ., 2019c), Basiria Siddiqi, 1959 (Eisvand et al ., 2019) and Malenchus Andrássy, 1959 (Jalalinasab et al ., 2019) have since been reported or described from Iran through morphological and molecular studies. The present study aims to describe the newly recovered species, named Thada populus n.…”
Section: Introductionmentioning
confidence: 99%